The STRATEGI KOMUNIKASI ORGANISASI DALAM PELAKSANAAN PROGRAM KERJA HIMPUNAN MAHASISWA MICRO IT SEKOLAH VOKASI IPB - Anchar, Najla Aulia; Suparman, Suparman; Julia Andriani, Yafnida; Putri Awalina, Salwa (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
This study analyzes the communication strategies employed by the Micro IT Student Association at IPB University in executing their work programs. Using a descriptive qualitative approach, in-depth interviews were conducted with key members of the organization to explore their communication practices and the challenges they face. The findings reveal that transparency and openness are fundamental strategies, fostering engagement and collaboration among members. Regular meetings serve as a crucial platform for discussing progress and addressing issues, aligning with participatory communication theories. However, challenges such as social gaps and inadequate responses from members hinder effective communication. Recommendations include implementing informal discussion sessions and utilizing anonymous feedback platforms to improve member involvement and address communication barriers. Keywords: Communication Challenges, Communication Strategy, Engagement, Student Organization, Transparency